The Effect of Developmental Stages on the Photosynthetic Parameters of the Melon - Nifi, Agayev Faxraddin; İlham, Allahverdiyev Elmar; Hajı, Mammadova Khurshid; Agil, Yolchueva Emina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study explores the fluctuations in key photosynthetic parameters in two high-potential melon (Cucumis melo L.) cultivars—Gunash and Sadaf—grown in open-field conditions in the Absheron region. The research analyzes a range of physiological and biochemical traits, such as leaf area, photosynthetic potential (PP), net photosynthetic productivity (NPP), specific leaf surface density (SLSD), concentrations of plastid pigments, the coefficient of economic photosynthetic efficiency (CEEP), overall economic efficiency (CEE), and the accumulation of both fresh and dry biomass. Results show a steady rise in SLSD and biomass (both crude and dry) from the vegetative phase to fruit development and full ripening. The early-ripening Gunash cultivar displayed the highest gains during early fruit formation, while the mid-ripening Sadaf cultivar reached peak values during full ripening. Significant differences in NPP, SLSD, and CEE were found throughout the plant's life cycle, with peak values observed at the mass ripening stage in both varieties. Additionally, levels of chlorophyll and carotenoids in the leaves showed a three-phase peak pattern, with each phase varying by cultivar